HUBUNGAN BEBAN KERJA MENTAL DENGAN DEPRESI DAN CEMAS PADA PERAWAT ICU-NICU-PICU DI RS MITRA SEJATI: ANTIBACTERIAL EFFECTIVENESS OF TURMERIC RHIZOME ETHANOL EXTRACT (CURCUMA DOMESTICA VAL) AGAINST VIBRIO CHOLERAE GROWTH IN VITRO - Sitepu, Arneil; Siddiq, Muhraza; Siagian, Nurul Aini (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2025)
Vibrio cholerae is a Gram-negative, anaerobic bacterium. Cholera is an intestinal infection caused by Vibrio cholerae or contact with a cholera carrier. Turmeric rhizome (Curcuma domestica Val) extract is known to have antibacterial properties. Active compounds such as flavonoids, saponins, alkaloids, and tannins in turmeric rhizomes have been shown to inhibit the growth of Vibrio cholerae. This study aimed to evaluate the antibacterial effectiveness of turmeric rhizome extract (Curcuma domestica Val) against the growth of Vibrio cholerae in vitro. The research used a descriptive approach with experimental methods, conducted at the Microbiology and Organic Chemistry Laboratory, University of Sumatera Utara (USU). Extraction was performed using the maceration method. The study employed four different concentrations of turmeric rhizome extract: 25%, 50%, 75%, and 100%. Data collection involved treating Vibrio cholerae cultures with the extracts and measuring the diameter of the inhibition zones using a caliper. Data analysis was conducted using ANOVA and a Post Hoc Bonferroni test. Results showed that the 100% concentration of turmeric rhizome extract was the most effective in inhibiting the growth of Vibrio cholerae, with a p-value of 0.000, an average inhibition zone diameter of 22.2 ± 0.49 mm, and a categorization of